INVESTMENT INVESTMENT DECISION MAKING BASED ON VALUE AT RISK (VAR) ANALYSIS FOR STOCKS OF STATE OWN BANK IN INDONESIA - Sitorus, Suandi (Journal Economics & Business Atmajaya Indonesia, 2018)
The purpose of this journal is how to measurement the probability of the maximum risk level for stocks of state-owned banks in Indonesia. One consideration for investors to make an investments decision in stock instruments by monitoring the daily volatility movement and the trend. However, if there are some stocks that are believed in good return, at a glance it seems to have the same volatility, the same trend of movement, it will be a challenge for investors to determine which stocks are preferred to become investments. From the risk perspective by measuring the maximum probability of risk level in the future, it can be a consideration in making stock investment decisions that have the same movements and characteristics. Risk projection based on historical data with a certain time period can be calculated with Value at Risk (VaR) with a certain level of confidence. Thus the investment decision will be optimal. The Value at Risk model will calculate the expected losses. This research will show that volatility that looks the same but has a different level of risk. This research will measuring a useful value for prospective investors in determining investments among the stocks of state-owned banks in Indonesia. The data used in this study is the stock closing price that has been adjusted taken from the source of the website www.yahoo finance for the period 2015-2018. This study stipulates that the VAR model is the maximum risk estimate that may arise with a 95% confidence level, or an error rate that is tolerated at 5%. The VaR method used is historical analysis.